Central Application of Aliskiren, a Renin Inhibitor, Improves Outcome After Experimental Stroke Independent of Its Blood Pressure Lowering Effect - Panahpour, Hamdollah; Terpolilli, Nicole A.; Schaffert, David; Culmsee, Carsten; Plesnila, Nikolaus (Frontiers in Neurology, 2019)
Epidemiological studies suggest that pharmacological reduction of systemic hypertension lowers incidence and severity of stroke. However, whether the reduction of blood pressure per se or the compounds used to reduce hypertension are responsible for this effect received little attention. In the current study we therefore aimed to investigate whether Aliskiren, a renin-inhibitor used to treat arterial hypertension, may improve outcome in a mouse model of ischemic stroke when applied centrally and in a dose not affecting blood pressure. Male C57BL/6 mice received 0.6, 2.0, or 6.0 µg Aliskiren or vehicle by intracerebroventricular injection as a pre-treatment and were then subjected to 60 min of middle cerebral artery occlusion (MCAo). Infarct volume, brain edema formation, mortality, antioxidant effects, and functional outcome were assessed up to seven days after MCAo. Central administration of Aliskiren (0.6 or 2.0 µg) had no effect on systemic blood pressure but significantly reduced infarct volume and brain edema formation, blunted mortality, and improved neurological outcome up to one week after MCAo. Due to the central and prophylactic administration of the compound, we cannot make any conclusions about the potency of Aliskiren for acute stroke treatment, however, our study clearly demonstrates, that in addition to lowering blood pressure Aliskiren seems to have a direct neuroprotective effect. Hence, renin-inhibitors may be an effective addition to prophylactic treatment regimens in stroke patients.